Linking AMO-Based HRM to Corporate Sustainability: The Mediating Role of Staff Performance in Healthcare Organizations - Saputro, Gabrielle; Sorongku, Ronald (International Review of Management and Marketing, 2026)
This study aims to examine the effect of Ability–Motivation–Opportunity (AMO) on Corporate Sustainability, through Staff Performance as a mediating variable. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The sample consisted of 184 respondents selected using a purposive sampling technique. Data were analyzed to assess the relationship between constructs and evaluate the mediating role of Staff Performance. The results indicate that AMO has a significant positive effect on Staff Performance and Corporate Sustainability. In addition, Staff Performance significantly influences Corporate Sustainability and partially mediates the relationship between AMO and Corporate Sustainability. The findings also show that AMO is the most dominant factor influencing organizational outcomes, highlighting the importance of employee capability, motivation, and opportunity in driving sustainable organizational performance. Additionally, the model demonstrates moderate explanatory power, confirming the relevance of human resource practices in enhancing sustainability outcomes. The study concludes that strengthening AMO practices is essential to improve employee performance and achieve long-term corporate sustainability. However, the research is limited by its cross-sectional design and single-organization context, which may limit the generalizability of the findings. Future research is recommended to adopt longitudinal designs and broader industry samples to enhance external validity.